2018
DOI: 10.1101/301135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic regulation of the circadian genePer1in the hippocampus mediates age-related changes in memory and synaptic plasticity

Abstract: Aging is accompanied by impairments in both circadian rhythmicity and long-term memory.Although it is clear that memory performance is affected by circadian cycling, it is unknown whether age-related disruption of the circadian clock causes impaired hippocampal memory.Here, we show that the repressive histone deacetylase HDAC3 restricts long-term memory, synaptic plasticity, and learning-induced expression of the circadian gene Per1 in the aging hippocampus without affecting rhythmic circadian activity pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Similar results were obtained in mice kept in constant darkness (Figures S1C and S1D). These results are consistent with previous studies in the hippocampus of 4-to 6-month-old mice and in hippocampal slice cultures and expand them, showing that the transcriptiontranslation feedback loops responsible for the circadian regulation of clock gene expression are functional also in the hippocampus of juvenile mice (Kwapis et al, 2018;Namihira et al, 1999;Wang et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained in mice kept in constant darkness (Figures S1C and S1D). These results are consistent with previous studies in the hippocampus of 4-to 6-month-old mice and in hippocampal slice cultures and expand them, showing that the transcriptiontranslation feedback loops responsible for the circadian regulation of clock gene expression are functional also in the hippocampus of juvenile mice (Kwapis et al, 2018;Namihira et al, 1999;Wang et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…Stably transfected cells were selected with puromycin (Sigma-Aldrich, St Louis, MO, USA). In addition, lentiviral vectors expressing human PER1 (Lv-PER1), P53 (Lv-P53), YTHDF2-specific shRNA (shYTHDF2), empty vectors (vector), and plasmids containing scrambled shRNA (scramble) were constructed as previously described [25][26][27].…”
Section: Vector Construction and Transductionmentioning
confidence: 99%
“…Since RCAN1 is known to both inhibit and facilitate CaN function (Vega et al, 2003;Liu et al, 2009;Wong et al, 2015) and to act independently of CaN (Keating et al, 2008), future studies are needed to determine how CaN participates in RCAN1-mediated daily activity rhythm disruptions associated with DS, AD, and aging. Moreover, it will be informative to assess rhythmic changes in hippocampal CaN activity, considering that the hippocampus contains an autonomous molecular clock that has been linked to memory performance (Kondratova et al, 2010;Smarr et al, 2014;Kwapis et al, 2018), and since hippocampus-dependent memory de cits were previously observed in both Rcan1 KO (Hoeffer et al, 2007) and RCAN1 TG (Wong et al, 2015) mice. Furthermore, pro ling the rhythmicity of RCAN1 levels and RCAN1-dependent modulation of CaN activity in other brain regions, such as the SCN, will be essential to establish if RCAN1 differentially regulates rhythmicity throughout the brain and to delineate the mechanisms whereby RCAN1 regulates diurnal and circadian activity patterns and rhythms.…”
Section: Discussionmentioning
confidence: 99%